DO INSTRUCTION AND EXPOSURE MAKE A DIFFERENCE ON THE LEARNING OF ORTHOGRAPHIC SPELLING BY SPEAKERS OF A REGIONAL VARIETY? - Balcom, Patricia (Linguistica Atlantica, 2008)
Referential French is a complex written code acquired at school by speakers of vernacular varieties (Barbaud 1997). The goal of this study is to investigate the influence of instruction and exposure on subjects’ production of several elements of Referential French which Lefran ois, Laurier, Lazure, and Claing (2005) showed to be problematic and which showed improvement after instruction, that is l’orthographe grammaticale ’grammatical spelling’. Grammatical spelling is an aspect of spelling in French which involves inflected forms of words. A controlled-production task was administered to 80 speakers of New Brunswick Acadian French who were students at a francophone university in the Maritime Provinces. There were 40 subjects in their first year of studies and 40 in their fourth or subsequent year. A number of aspects of orthographic spelling were examined: verb forms in the passe simple, past participial forms and agreement, and subject-verb agreement. Results showed that while there was still variability in the fourth-year students’ use, their performance was significantly closer to Referential French than that of the first-year students.